2012
DOI: 10.1002/pssc.201100813
|View full text |Cite
|
Sign up to set email alerts
|

Secondary electron emission yield (SEY) in amorphous and graphitic carbon films prepared by PLD

Abstract: High secondary emission yield (SEY), and the subsequent build‐up of a secondary electron cloud, may severely limit the stability of high‐intensity particle beams inside particle accelerators. One of the best candidates of beam pipe coating for reduced SEY has been amorphous carbon (a‐C) produced by direct current (D.C.) magnetron sputtering. Here we used pulsed laser deposition (PLD), to prepare a‐C films from a pure carbon target at substrate temperatures ranging from 300 K to 773 K. The ablating laser was a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…B). It is known that the SE yield for carbon structures varies and is higher in amorphous carbon films (∼1.95) (Alberti et al ., ) than for crystalline MWCNTs (∼0.6) (Alam et al ., ). This suggests that the brightness of cells should be higher than the MWCNTs; indeed, the situation is possible as indicated by the overlapping error bars in Figure (C) (data for image in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…B). It is known that the SE yield for carbon structures varies and is higher in amorphous carbon films (∼1.95) (Alberti et al ., ) than for crystalline MWCNTs (∼0.6) (Alam et al ., ). This suggests that the brightness of cells should be higher than the MWCNTs; indeed, the situation is possible as indicated by the overlapping error bars in Figure (C) (data for image in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades, large amounts of related research about a-C film have been carried out because of its relatively low SEY and simple deposition process. For example, M. Alberti et al produced an a-C film by pulsed laser deposition, and its maximum SEY is as low as 1.4 [28]. Vallgren et al prepared an a-C film by direct current magnetron sputtering and found that the SEY rose by 10–20% after this film exposed to air for one month [29].…”
Section: Introductionmentioning
confidence: 99%
“…The build-up of electron cloud generated by residual gas ionization, synchrotron radiation, etc., in the beam pipes considerably affects the stability of particle beams in a particle accelerator. For example, the suppression of secondary electron emission is important for the Super Proton Synchrotron (SPS) accelerator and the future super proton-proton collider (SPPC) [1][2][3][4]. Therefore, it is critical to look for stable and very low SEY material for future high intensity accelerators.…”
Section: Introductionmentioning
confidence: 99%